Implementasi Good Village Governance dalam Pengembangan Industri Pariwisata - I Made Arie Widyasthana Wartana Putra; Mohammad Nurul Huda (Nakhoda: Jurnal Ilmu Pemerintahan, 2022)
The implementation of Law Number 6 of 2014 concerning Villages is a form of independent and competitive rural development reform. The village law is a manifestation of granting authority and authority to villages in managing, managing, and regulating finances through the Village Fund Allocation (ADD). With the success of rural development reform, GVG has become a fundamental instrument in managing village finances. Unfortunately, previous research does not explain GVG as an effort to realize the development of the village tourism industry in Indonesia. This study seeks to provide literature through an analysis of the implementation of the principles of GVG to encourage the tourism industry’s success with a case study in Pujon Kidul Tourism Village, Malang Regency. Because the Pujon Kidul Tourism Village can develop tourism potential through managing village funds to increase Village Original Income (PADes) in Village-Owned Enterprises (BUMDES). The method used is a case study qualitative research with data collection techniques using in-depth interviews with stakeholders in Pujon Kidul Tourism Village. The research findings reveal that implementing GVG in Pujon Kidul Tourism Village in terms of transparency, accountability, and participation is marked by open discussions with the community through village deliberation forums. Responsibilities related to reporting funds sourced from APBDes, village funds, and other aid funds are also reported to the community verbally and in writing which is carried out at village deliberation forums. Meanwhile, the role of the community is still low because it still depends on the part of the village government.